(untitled) (Chittagong University Journal of Biological Sciences, 2024)
Adolescence is a period of stress and storm in which adolescents have to adjust with different physical, social, and psychological changes. If any adolescent fails to cope with these changes, then they may undergo various psychological challenges such as loneliness, aggression, emotional instability, etc. The present study aimed to know the nature of loneliness and aggression among adolescents as a function of adolescents developmental stages, medium of institution, and gender.120 participants were selected purposively in the age range 10-21 years (M=15.5±3.61). The present study showed that early adolescents scored more loneliness than the middle and late adolescents (F (2,108) =154.83, p<.001) and male adolescents scored more than the female adolescents (F (1,108) =44.23, p<.001). There was significant interaction effect among the stages of adolescents, medium of institution and gender (F (2,108) =6.85, p<.002) from loneliness viewpoint. Early adolescents showed more aggression than the middle and late adolescents (F (2, 108) = 336.45, p<.001). English medium students showed more aggression than the Bangla medium students (F (1,108) =55.53, p<.001). Male adolescents were more aggressive than female adolescents (7(1, 108) = 52.83, p<.001). A significant interaction effect on aggression was found between stages of adolescent and gender (F (2,103)-3.69, p<.03), and medium of institution and gender (F(2, 108)=6.85,p<.001). Finally, our results showed a significant positive correlation (r=,80, p<.01) between loneliness and aggression of adolescents. The Chittagong Univ. J. B. Sci. 9(1&2):153-166,2019